(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The main role in the process of forming a valuable attitude to one’s own health among student youth belongs to higher educational institutions, since the process of conscious formation of the basis of physical and mental health takes place directly in the student years, their needs and motives regarding the use of physical exercises are clarified and selected maintaining one’s own health and learning the values of a healthy lifestyle. Thanks to the means of physical culture, which play a critical role in the formation of a healthy lifestyle among young people, it can be argued that physical activity improves physical health. After all, regular physical exercises and training help strengthen muscles, improve endurance and the cardiovascular system. It also helps reduce the risk of developing heart disease, obesity and other diseases. Physical education helps reduce stress and anxiety, improve mood, and increase energy. It helps the youth to cope with the challenges of learning and maintain a positive mental state. Participation in sports teams and group classes promotes the development of communication and cooperation skills. Through physical education, young people learn about the importance of healthy eating, giving up bad habits and regular physical activity. These habits become an integral part of their daily life. By achieving new athletic goals and improving physical performance, youth develop self-confidence, self-discipline, and self-control. This helps them grow as individuals and achieve success in various areas of life. Therefore, means of physical culture are an integral part of a healthy lifestyle of young people. By combining different types of physical activity and sports activities, young people can develop not only physical, but also mental, social and emotional well-being, which creates the basis for their successful and happy future.